The Role of IL-36 in the Pathophysiological Processes of Autoimmune Diseases - Chen, Wen-jian; Yu, Xiao; Yuan, Xin-Rong; Chen, Bang-jie; Cai, Na; Zeng, Shuo; Sun, Yuan-song; Li, Hai-wen (Frontiers in Pharmacology, 2021)
A member of the interleukin (IL)-1 superfamily was IL-36, which contained IL-36α, IL-36β, IL-36γ, and IL-36Ra. Heterotrimer complexes, consisting of heterodimeric receptor complexes and IL-36 agonist, gave signals through intracellular functional domains, so as to bind to downstream proteins and induce inflammatory response. IL-36 agonists upregulated mature-associated CD80, CD86, MHCII, and inductively produced several pro-inflammatory cytokines through the IL-36R-dependent manner in dendritic cells (DCs). Besides, DCs had the ability to initiate the differentiation of helper T (Th) cells. Up to date, the role of IL-36 in immunity, inflammation and other diseases is of great importance. Additionally, autoimmune diseases were characterized by excessive immune response, resulting in damage and dysfunction of specific or multiple organs and tissues. Most autoimmune diseases were related to inflammatory response. In this review, we will conclude the recent research advances of IL-36 in the occurrence and development of autoimmune diseases, which may provide new insight for the future research and the treatment of these diseases.